(untitled) (International Journal of Innovative Technologies in Economy, 2022)
Among the essential elements of knowledge management is the use of information and data, as well as the knowledge, skills, and abilities inherent within communities, as well as their ideas, commitments, and motivations for making good decisions as emerging technologies become more prevalent. Numerous leading social scientists in this field have asserted that organizational knowledge should be regarded as a strategic asset. There is a growing awareness of the importance of gathering, locating, capturing, and sharing collective knowledge and expertise of societies, and societies are urged to develop effective and efficient methods of gathering, locating, capturing, and sharing that knowledge in order to deal with problems and to benefit from opportunities. People living in many countries and regions are interested in implementing knowledge management processes and technologies, and many of them have included knowledge management as an integral part of their overall development strategies. The management of knowledge plays an increasingly important role in global economic development (Bell, 1973, 1978). In order to remain relevant in the modern world, organizations should not ignore knowledge management and emerging technologies.